2008
DOI: 10.1007/s00441-008-0666-9
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of static-load-degenerated articular cartilage extracellular matrix by vitamin C supplementation

Abstract: The effect of a physiological dose of vitamin C (100 microg/ml) on goat articular cartilage chondrocytes cultured in an alginate matrix and subjected to static pressurization of 2.4 MPa was investigated. Biochemical analyses of DNA, glycosaminoglycan (GAG), collagen and protease activity were carried out in various matrix fractions, i.e. cellular matrix (CM) and further removed matrix (FRM), and in culture medium. The treatment of chondrocytes with vitamin C after static pressure increased the GAG content in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Gallagher et al [6] also reported no evidence in the literature to support or refute their use for chondroprotection. Earlier however, Kraus et al [7] showed ascorbic acid increased rather than decreased the severity of spontaneous osteoarthritis in animals as discussed by Sharma et al [8], and Chaganti et al [9] found higher serum vitamin C levels in cases of knee osteoarthritis with more rapid disease progression.…”
Section: Novel Techniques In Arthritis and Bone Researchmentioning
confidence: 96%
See 1 more Smart Citation
“…Gallagher et al [6] also reported no evidence in the literature to support or refute their use for chondroprotection. Earlier however, Kraus et al [7] showed ascorbic acid increased rather than decreased the severity of spontaneous osteoarthritis in animals as discussed by Sharma et al [8], and Chaganti et al [9] found higher serum vitamin C levels in cases of knee osteoarthritis with more rapid disease progression.…”
Section: Novel Techniques In Arthritis and Bone Researchmentioning
confidence: 96%
“…This suggests that low doses of ascorbate are extremely effective compared to higher dose concentrations. An in vitro study by Sharma et al [8] further showed that vitamin C supplementation of chondrocytes after static loading reduced the normal degenerative processes of these cells caused by static loading, thereby improving the cellular health and functioning of articular cartilage. Likewise, Koike et al [16] found a vitamin C derivative to effectively suppress mitochondrial superoxide generation and delayed cartilage degeneration in a mechanical overload model, and which appears to be of considerable utility.…”
Section: Novel Techniques In Arthritis and Bone Researchmentioning
confidence: 99%
“…The production of the extracellular matrix during the healing process following damage or infection of tissue also relies on vitamin C [ 22 ]. It is responsible for hydroxylating proline and lysine within newly formed collagen, allowing it to mature and stabilize the tissue of a healing wound [ 34 ]. Lack of vitamin C leads to this process being compromised.…”
Section: Reviewmentioning
confidence: 99%
“…Another potent antioxidant, vitamin C (ascorbic acid), has a broad spectrum of antioxidative activities, owing to its ability to scavenge numerous ROS [14] . It also acts as a cofactor for numerous biochemical reactions and is essential for collagen biosynthesis [15] . A preclinical study on surgically induced OA in guinea pigs [16] and an epidemiological study on OA patients [17] , both suggested that high dietary intake of vitamin C reduced the risk of cartilage loss and delayed disease progression.…”
Section: Introductionmentioning
confidence: 99%